1994
DOI: 10.1080/10862969409547861
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Unknown Vocabulary Words in Text as a Function of the Relative Difficulty of the text: Implications for Instruction

Abstract: The relationship between the relative difficulty of passages and the number of unknown words in passages was investigated. In Study I, 219 students in Grades 3, 4, 5, and 6 were given 100-word passages sampled from textbooks and library books (trade books) and then asked to underline each word that they did not know. In Study II, 60 graduate students were given a similar task involving 120 passages at the following levels of difficulty: junior high, senior high, college, and graduate school. Relative difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 16 publications
7
127
2
9
Order By: Relevance
“…This means that learners need to have simplified reading material of various levels in order to learn from meaning-focused input and to develop fluency in reading if they are to learn from these strands at all stages of their second language development". Carver (1994) points out that learners will increase their vocabulary size through reading only with material that is not too easy so that they have opportunities to encounter new words. Reading easy texts may serve the purpose of deepening vocabulary knowledge, but not the purpose of increasing vocabulary size.…”
Section: Discussionmentioning
confidence: 99%
“…This means that learners need to have simplified reading material of various levels in order to learn from meaning-focused input and to develop fluency in reading if they are to learn from these strands at all stages of their second language development". Carver (1994) points out that learners will increase their vocabulary size through reading only with material that is not too easy so that they have opportunities to encounter new words. Reading easy texts may serve the purpose of deepening vocabulary knowledge, but not the purpose of increasing vocabulary size.…”
Section: Discussionmentioning
confidence: 99%
“…That's to say, the coverage of unknown word rate is about 2.2%. Nation (1990) and Laufer (1997) put forward that mastery of 95% known words in a text is necessary for general text comprehension, and Carver (1994) found that difficult reading materials contained around 2% or more unknown words and materials for pleasant reading contained around 1% unknown words. According to these findings, this reading material was a perfect one for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Au cours de la lecture, une fréquence même relativement faible de « mots inconnus » (18) suffit à compliquer le décodage et à entraver la compréhension (Carver, 1994) ; mais l'activité de lecture représente en elle-même un élément important pour l'acquisition lexicale ; les recherches ont montré qu'il est néces-saire que le lecteur rencontre un lexème à de nombreuses reprises, et dans diffé-rents contextes pour construire progressivement son sens (Nagy et al, 1985(Nagy et al, , 1987a. La lecture fournit une autre porte d'entrée au lexique : comme le remarque David (2000), au cours de l'apprentissage de la lecture le lexique oral est reconfiguré par l'acquisition des formes écrites, notamment dans sa dimension morphologique ; il y a aussi une interaction évidente entre l'appropriation de certains genres propres à l'écrit et le développement des répertoires lexicaux.…”
Section: Le Lien Avec Les Activités De Lectureunclassified